The study of visual interface aesthetics in educational website Kansei engineering approach - Nur Faraha Hj. Mohd. Naim (2016)
E-Learning or educational website can be described as a ubiquitous platform for broad dissemination of knowledge. The educational website must be convenient and entertaining for students to utilize and experience the said website concerning their studies. Nevertheless, what educational website could offer for students might deter due to the lackadaisical of design on the web interface. There are times when the design interface and the mixture of multimedia elements applied on the particular websites may affect the students’ tendency to use them. In accordance with that context, the objectives of this research are to: i. Investigate the student’s emotional awareness on visual interface aesthetics based on the gender preferential reaction; ii. Evaluate the degree of preferable interface design concepts applied on the educational website; iii. Ascertain the appropriate extent of multimedia elements used for an educational website; and iv. Measure the correlation between motivation and utilization on the educational website concerning visual interface aesthetics. Kansei Engineering (KE) Approach was used for measuring the feelings response toward interface design to obtain the results. The proceedings in finding the design criteria began with the selection of web interface design. In furtherance to counterbalance the research hypothesis, the design scope had to be narrowed down into three designs; Colour-based Design, Grid-based Design (Layout) and Text-based Design. As a result, the response varies from one person to another according to gender differences. The result indicated that female students have the tendency of showing their emotional reaction rather than male students albeit that both genders indeed had mutual subjective agreement on Colour-based Design for an educational website. Other than that, male students prefer graphics on the website whilst female students prefer text. Despite having diversity response towards the said interface, the correlation between motivation and utilization are moderate enough to influence their interest and decision whether to utilize the educational website or otherwise.